2001
DOI: 10.1111/j.1746-1561.2001.tb06486.x
|View full text |Cite
|
Sign up to set email alerts
|

Health‐Risk Behaviors Among Middle School Students In A Large Majority‐Minority School District

Abstract: Since 1991, the Centers for Disease Control and Prevention has administered the Youth Risk Behavior Survey (YRBS) biennially to representative samples of high school students. YRBS results indicate that health-risk behaviors often developed during middle school years. To date, few state and local education agencies have administered the YRBS-Middle School. This study measured prevalence of health-risk behaviors among middle school students in a large, majority-minority school district (n = 1,783). Results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
14
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 5 publications
4
14
0
1
Order By: Relevance
“…Similar to other research results, many health risk behaviours were found to be interrelated rather than being a collection of independent activities (Brenner and Collins 1998; Potthoff et al 1998; Fetro et al 2001; Anteghini et al 2001; Shrier et al 1997). Almost one third of the junior high school students and around 60% of the senior high school as well as university students were involved in more than one risk behaviour.…”
Section: Discussionsupporting
confidence: 84%
“…Similar to other research results, many health risk behaviours were found to be interrelated rather than being a collection of independent activities (Brenner and Collins 1998; Potthoff et al 1998; Fetro et al 2001; Anteghini et al 2001; Shrier et al 1997). Almost one third of the junior high school students and around 60% of the senior high school as well as university students were involved in more than one risk behaviour.…”
Section: Discussionsupporting
confidence: 84%
“…A study of ethnically diverse urban middle school students, for example, found 31% of those who smoked a cigarette had done so by age 9 years, and 47% had their first drink of alcohol by age 9 years. 6 During the 1990s, the major causes of mortality and morbidity for youth shifted from infectious to behavioral causes related to such risky activities. 7 Several models suggest that the increase in these behaviors during early adolescence is a result of both personal characteristics and environmental conditions.…”
mentioning
confidence: 99%
“…While the high school version of the YRBS has been used to describe suicide among high school age youth (eg, Grunbaum et al 13 and Eaton et al 12 ), less is known about suicidal behaviors in middle school students. Studies using the middle school YRBS have indicated that many risky behaviors are adopted during these early teenage years, 22‐24 so the availability of such information may allow for interventions to minimize the adoption of high‐risk behaviors. We hypothesized that perception of overweight would be significantly associated with suicidal thoughts and actions when controlling for important personal and family characteristics.…”
mentioning
confidence: 99%